Application based solutions for trading companies to analyse tax corrections - Koerniawan Dwi Wibawa; Sugiharto; Tri Septianto (Inovasi Analisis Data, 2024)
Purpose – This study analyses the implications of application-based solutions in attaining uncomplicated fiscal corrections for trading companies. It elucidates on the necessity of digitalization for tax corrections, its efficient tax re-adjustment measures and standard application models of tax compliance.Design/methodology/approach – This study analyses the implications of application-based solutions in attaining uncomplicated fiscal corrections for trading companies. It elucidates on the necessity of digitalization for tax corrections, its efficient tax re-adjustment measures and standard application models of tax compliance.Findings – The findings determine that the correction mechanisms have advanced accuracy, transparency and compliance while eliminating manual errors and curtailing administrative loads. The research outlines common challenges faced by companies in undertaking fiscal corrections and indicates areas for technology led solutions to enhance efficiency.Originality/value – This research provides the literature on financial digitalization with hands-on implications of technology integration within financial governance. These findings, therefore, offer useful insights for companies and legislators to streamline fiscal compliance with the help of application-based interventions.Research Implications – This study emphasizes the need for digital transformation in tax correction processes and indicates that organizations that adopt technology would be acknowledged showcasing enhanced efficiency and competitive advantage. Subsequent studies may broaden the focus to include a range of sectors and employ quantitative techniques to improve for generalizability.